Inactivation and Mutagenesis of Tobacco Rattle Virus by Nitrous Acid - Robinson, D. J. (Journal of General Virology, 1973)
SUMMARY The rate of inactivation of tobacco rattle virus RNA by 0.2 m-nitrous acid at pH 4.0 was comparable to that of tobacco mosaic virus RNA. In 0.0025 m-nitrous acid at pH 6.0 this rate was greatly diminished, and was slower than that of intact virus. Possible reasons for this are discussed. Methods are described for the induction of mutants of tobacco rattle virus by nitrous acid, and for the selection of temperature-sensitive mutants that are not characterized by changes in the coat protein gene.